Explaining growth paths of young technology‐based firms: structuring resource portfolios in different competitive environments - Clarysse, Bart; Bruneel, Johan; Wright, Mike (Strategic Entrepreneurship Journal, 2011)
Abstract We explore how environmental contingencies determine the way resources are accumulated in young technology‐based firms and argue that growth paths are critically shaped at the nexus between resource management and the competitive environment, defined along its most important dimensions, ‘stability’ and ‘complexity.’ We also build propositions about the way environmental conditions affect resource portfolio development or acquisition. We show how particular high‐growth paths result from structuring resource portfolios in accordance with environmental demands and provide insights into why, based on six case studies of young technology‐based high‐growth firms, involving 27 interviews, 121 press releases, 605 press articles, and archival data. Copyright © 2011 Strategic Management Society.